Quantitative integrative taxonomy informs species delimitation in Teloschistaceae (lichenized Ascomycota): the genus Wetmoreana as a case study - Karina Wilk; Robert Lücking (IMA Fungus)
Abstract The genus Wetmoreana was studied using quantitative integrative taxonomy methods to resolve the genus delimitation and explore its taxonomy diversity at the species level. As a result, the genus Fulgogasparrea is synonymized with Wetmoreana, and the latter includes 15 formally described species, one subspecies, and three further, thus far undescribed species: W. appressa, W. awasthii comb. nov., W. bahiensis sp. nov., W. brachyloba comb. nov., W. brouardii, W. chapadensis comb. nov., W. circumlobata sp. nov., W. decipioides, W. intensa comb. nov., W. ochraceofulva comb. nov., W. rubra sp. nov., W. sliwae sp. nov., W. sliwae ssp. subparviloba subsp. nov., W. subnitida comb. nov., W. texana, and W. variegata sp. nov. Eleven of 19 examined taxa are newly placed within this genus or confirmed to belong to it. Two species, W. awasthii and W. intensa, are transferred to Wetmoreana without additional analysis but based on previous studies. The W. brouardii and W. ochraceofulva species complexes are discussed in detail. Additionally, Caloplaca muelleri and C. rubina var. evolutior are transferred to Squamulea, and the latter is elevated to the species rank.